Comparison of safety outcomes between bi-coronal and direct approaches for device removal in patients treated with distraction osteogenesis for craniosynostosis. Issue 3 (March 2022) - Jeon, Sungmi; Kang, Jiwon; Chung, Jee Hyeok; Kim, Sukwha; Kim, Seung-Ki; Phi, Ji Hoon; Lee, Ji Yeoun; Kim, Kyung Hyun; Wang, Kyu-Chang; Kim, Byung Jun
Abstract: The study aimed at comparing the safety outcomes between conventional bicoronal and direct method in device removal after cranial distraction in the treatment of craniosynostosis. This was a retrospective cohort study of patients treated with distraction osteogenesis to expand intracranial volume in the anteroposterior direction. Preoperative patient demographics, distraction protocols, and perioperative outcomes (operative time, estimated blood loss, intraoperative fluid volume, lowest hematocrit during surgery, transfusion, hospital stay, drain, postoperative complication) were collected and analyzed with the independent samples t -test. Twenty-four patients were included in the study (15 in the conventional and 9 in the direct approach group). The mean duration of surgery and intraoperative fluid volume were significantly shorter (114.56 ± 36.91 min vs. 177.20 ± 47.00 min, p = 0.003) and less (241.88 ± 194.07 ml vs. 624.00 ± 524.92 ml, p = 0.026), respectively in the direct group than in the conventional. No patients were transfused intraoperatively and admitted to the intensive care unit (ICU) postoperatively in the direct group. The mean intraoperative and total transfusion volumes were significantly greater in the conventional group (p = 0.004, 0.045, respectively). There were no significant differences in other safety outcomes. No postoperative wound complications were reported. The findings of this study indicated that the direct approach for distraction device removal in children with craniosynostosis appears to be safer than the conventional approach owing to the reduced operation time, intraoperative transfusion requirements, and ICU stay.